Organizing lesbian/queer bathhouse events: Emerging forms of sexual experience. - Brown, A D; Gailey, Nerissa (Journal of Lesbian Studies, 2016)
Discussions of public sexual spaces in the social science literature have, until recently, been dominated by analyses of men's use of these spaces for erotic expression. In the late 1990s, feminist collectives began to explore the emancipatory potentials these spaces can have for lesbian sexualities. After a police raid on one such event called the "Pussy Palace," scholars in diverse disciplines began to explore how these events have both opened up and restricted erotic possibilities for lesbians, queer women, and trans* attendees. This article reviews the existing social science literature on lesbian and queer bathhouse events and highlights several key themes and subthemes that have dominated the discourse, including the importance that these spaces be recognized for their ability to both shape and be shaped by principles of community, safety, and sexual health/wellness.
3 citations (Crossref) [2023-10-31] Place: England Brown, A D. a Department of Sociology, Southern Connecticut State University, New Haven, Connecticut, USA. Gailey, Nerissa. b Department of Sociology and Anthropology, Mount Saint Vincent University, Halifax, Nova Scotia, Canada.
Keywords: *Homosexuality; Female; *Homosexuality; Male; *Public Facilities; *Sexual Behavior; Baths; Female; Homosexuality; Female; Homosexuality; Male; Humans; Lesbian; Male; Public Facilities; Sexual Behavior; Social Behavior; bath; bathhouse; dept.soc; ethic of care; female; human; lesbianism; male; male homosexuality; public sex; sanitation; sexual behavior; sexual politics; social behavior